2007
DOI: 10.1177/1359104507078477
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Drama Therapy Program for Immigrant and Refugee Adolescents: A Pilot Study

Abstract: This evaluative study assesses the effects of a school drama therapy program for immigrant and refugee adolescents designed to prevent emotional and behavioral problems and to enhance school performance. The 9-week program involved 136 newcomers, aged 12 to 18, attending integration classes in a multiethnic school. Pretest and posttest data were collected from the students and their teachers. The self-report and teacher's forms of the Strengths and Difficulties Questionnaire were used to assess emotional and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
172
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(185 citation statements)
references
References 24 publications
3
172
1
4
Order By: Relevance
“…This program also appeared to be associated with "a decrease in impairment in girls, while the program appeared to prevent an increase in impairment in boys." 26 …”
Section: Summary Of Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This program also appeared to be associated with "a decrease in impairment in girls, while the program appeared to prevent an increase in impairment in boys." 26 …”
Section: Summary Of Study Findingsmentioning
confidence: 99%
“…27 Two articles discussed a program and an intervention designed for immigrant and refugee adolescents in schools. The first evaluated a 9-week school drama therapy program 26 and the second evaluated an intervention involving a 12-week series of workshops integrating drama and language awareness. 29 Both of these studies reported post-program/intervention reductions in impairment related to emotional and behavioural symptoms among participants compared with comparison groups.…”
Section: Summary Of Study Findingsmentioning
confidence: 99%
“…Rather they showcase interventions that either: a) have a well-developed parent component, b) have strong research support, or c) are specifically designed for groups that have not traditionally been the focus of mental health treatment programs (such as Asians or children living in foster care). More information on treatment programs for immigrant families is available from the National Child Traumatic Stress Network (2005) and is reported in Rousseau, Benoit, Gauthier, Lacroix, Alain, et al (2007). Additional information on evidence-based mental health treatment for children in the CWS is reported in Shipman and Taussig (2009).…”
Section: Purposementioning
confidence: 98%
“…A common denominator in these studies is that they measure the impacts of being exposed to war and violence in various parts of the world, and the effects upon the mental health of children. Research has also focused on various programs targeting these children in the new country through various interventions based on CBT, expressive therapies, and other school-based mental health interventions (Rousseau et al 2007;Baker & Jones 2006;Ehntholt et al 2005;Fazel et al 2009;O'Shea et al 2000;Ruf et al 2010). These studies have evaluated the outcomes and effects on children attending various programs as a means to find better ways to meet their needs.…”
Section: Children Within Migration Researchmentioning
confidence: 99%